Praktik Pemberian Makanan dan Praktik Kesehatan dengan Kejadian Balita dengan Gizi Kurang (Journal of Telenursing (JOTING), 2021)
This study aims to determine the relationship between feeding practices and health practices for under-five children with malnutrition in Sekip Village, Lubuk Pakam District, Deli Serdang Regency. This study used a cross-sectional approach with a sample size of 100 respondents. Sampling was done using cluster technique and simple random technique (roll of paper). The resulting data were analyzed univariate and bivariate using the chi-square test (Î± = 0.05). The results showed that under-fives who experienced malnutrition were 34%. Simultaneously, mothers' feeding practices and health practices to children under-five were partly categorized as bad, namely 56 people (56%) and 54 people (54%). In conclusion, there is a relationship between feeding practices and health practices on undernutrition in children under-five.Keywords: Toddler, Malnutrition, Health Practices, Feeding Practices